The Contextual Origin of Ibn Taymiyyah's Thought on Jihad - Hamdan Maghribi; Abbas Sofwan Matlail Fajar; Alfina Hidayah (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
Since the 1980s until today, Aḥmad ibn Taimiyyah (d. 1328) has been one of the most quoted medieval scholars by jihadists. From ‘Abd al-Salām Faraj (d. 1981) to Osama bin Laden and his al-Qaeda. Ibn Taimiyyah is frequently cited to justify their doctrine. Ibn Taimiyyah’s fatwa is used to declare a legitimate leader of a country an apostate for not fully implementing the shari’ah and obligating every Muslim to jihād against him, classifying war zones (dār al-ḥarb) and requiring emigration (hijrah) from them, and permitting suicide bombings in the name of jihād. This article examines jihadists’ understanding of jihād as well as Ibn Taimiyyah’s jihād fatwas, specifically the three anti-Mongol fatwas and the Mardin fatwa, which are frequently cited by jihadists. This article addresses two major issues: first, it discusses Ibn Taimiyyah’s three anti-Mongol fatwas, as well as their citation and interpretation in jihadist fatwas; second, it examines the Mardin fatwa, which is always used as justification for jihad against the legitimate government. The article finds that some of the radicalists’ jihād doctrines quote directly from Ibn Taimiyyah’s jihād fatwas, particularly the three anti-Mongol fatwas and the Mardin fatwa, but most of the fatwas cannot be associated with Ibn Taimiyyah when approached holistically. The article also notes that Ibn Taimiyyah’s jihād doctrine is only partially quoted and ignores the majority of fatwas that are closely related to the theme of jihād, such as the concepts of hijrah and critical loyalty to the government. This article also identifies Ibn Taimiyyah’s jihād fatwas as being more frequently cited to legalize the interests of jihadist groups in justifying their acts of terror while ignoring the historical and political contexts that surround them.